The relationship between the satisfaction with training and the attitude of soldiers towards career expectancy and job involvement - Montfort, Pierre Juan de (Bloemfontein: Central University of Technology, Free State, 2003)
The purpose of this study was to determine the relationship between the satisfaction with training and the attitude of soldiers towards career expectancy and job involvement at the Air Defence Artillery Formation of the SA Army is. The primary research question addressed by the study was: "What is the relationship between the satisfaction with training and the attitude of soldiers, at the Air Defence Artillery Formation of the South African Army, towards career expectancy and job involvement?" The first sub-problem was to determine whether there is a relationship between the satisfaction with training and the attitude of soldiers I towards career expectancy. The second sub-problem was to determine whether there is a relationship between the satisfaction with training and the attitude of soldiers towards job involvement. Sub-problem · three was to determine whether there is a relationship between the attitude of soldiers towards career expectations and job involvement. Surveyed were, four hundred and sixty seven (476) full time soldiers from the Air Defence Artillery School and 10 Anti-Aircraft Regiment using a 51 -item questionnaire. The satisfaction with training viewed as the independent variable divided in six sub-variables: planning, implementation, evaluation, vision and commitment, empowerment and general reactions. The Index of Organisational Reactions (lOR) scale (1 996) measured career expectancy. The Lodahl and Kejner Job Involvement Scale ( 1 965) assessed job involvement. Demographic data pertaining to gender, age, rank group, population group, and former force supplemented results. The researcher found that the satisfaction with training has a significant correlation with the attitude of soldiers regarding career expectancy and job involvement. Also found was a positive correlation between job involvement and career expectancy. Several recommendations for future research are given. This includes conducting a similar study at other units of the SA Army. Having established the importance of satisfaction with training, the researcher suggests that forging a link between training, career expectancy and work-related attitudes may well help the SA Army to move a step closer to a balanced and competent force; to explore further the use of job involvement and other work-related variables as potential outcomes of human resource development.
Thesis
Keywords: Soldiers - South Africa - Job satisfaction; Soldiers - Training of - South Africa; Soldiers - Rating of - South Africa; Soldiers - South Africa - Attitudes; Job security - South Africa